2020
DOI: 10.1002/mrd.23341
|View full text |Cite
|
Sign up to set email alerts
|

RS‐1 enhances CRISPR‐mediated targeted knock‐in in bovine embryos

Abstract: Targeted knock-in (KI) can be achieved in embryos by clustered regularly interspaced short palindromic repeats (CRISPR)-assisted homology directed repair (HDR). However, HDR efficiency is constrained by the competition of nonhomologous end joining.The objective of this study was to explore whether CRISPR-assisted targeted KI rates can be improved in bovine embryos by exposure to the HDR enhancer RS-1. In vitro produced zygotes were injected with CRISPR components (300 ng/µl Cas9 messenger RNA and 100 ng/µl sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 55 publications
(81 reference statements)
0
13
0
1
Order By: Relevance
“…After microinjection of the CRISPR components and an ssDNA repair template, in vitro fertilized zygotes were incubated in 7.5 µM RS-1. KI rates were doubled compared to embryos not treated with RS-1 [61]. Another recent study, however, did not observe an effect with RS-1 [41].…”
Section: Rad51mentioning
confidence: 79%
“…After microinjection of the CRISPR components and an ssDNA repair template, in vitro fertilized zygotes were incubated in 7.5 µM RS-1. KI rates were doubled compared to embryos not treated with RS-1 [61]. Another recent study, however, did not observe an effect with RS-1 [41].…”
Section: Rad51mentioning
confidence: 79%
“…In this perspective, early TE specification could have emerged as an evolutionary mechanism in rodents to allow implantation at an earlier stage than in other species. Fortunately, recent improvements in genome edition techniques in ungulates ( 39 , 40 ) currently allow the exploration of the molecular machinery involved in ICM/TE specification in farm animals. Genome editing constitutes also an unvaluable tool to study other reproductive processes ( 41 ).…”
Section: Molecular Control Of the First Cell Lineage Differentiationsmentioning
confidence: 99%
“…Small molecules treatments to increase KI efficiency have been reviewed (Yeh et al, 2019;Bischoff et al, 2020). No data was reported to date in rats or mice, and only two studies showed that RS-1 enhances KI efficiency in rabbit (Song et al, 2016) and bovine embryos (Lamas-Toranzo et al, 2020). Finally, tests on cells and mouse embryos have shown that ExoI overexpression enhances KI activity (Aida et al, 2016).…”
Section: Repair Pathwaysmentioning
confidence: 99%